Brain anatomy of autism spectrum disorders I. Focus on corpus callosum. (26th March 2013) - Bellani, M.; Calderoni, S.; Muratori, F.; Brambilla, P.
Abstract : This brief review aims to examine the structural magnetic resonance imaging (sMRI) studies on corpus callosum in autism spectrum disorders (ASD) and discuss the clinical and demographic factors involved in the interpretation of results.